Application of Symbiotic Culture of Bacteria and Yeast Kombucha Gel on Incision and Burn Wounds in Mice (Mus musculus): Aplikasi Gel Symbiotic Culture of Bacteria dan Yeast Kombucha pada Luka Sayat dan Bakar Mencit (Mus musculus) - Funsu Andiarna; Irul Hidayati; Eva Agustina; Risa Purnamasari (JRST (Jurnal Riset Sains dan Teknologi), 2026)
SCOBY (Symbiotic Culture of Bacteria and Yeast) is a result of kombucha tea fermentation that contains active compounds, such as phenolic acids and flavonoids, which possess high antioxidant activity. However, the use of SCOBY is currently limited to serving as a starter culture for new batches of kombucha tea, necessitating innovation to enhance its other potential benefits. This study aims to evaluate the effectiveness of kombucha SCOBY gel in the healing of incised and burn wounds in mice (Mus musculus). The research methods included the preparation of kombucha tea, harvesting of SCOBY, formulation of gel, application of the gel to incised and burn wounds in mice, and observation of wound healing until closure. The results showed that kombucha SCOBY gel significantly accelerated the healing of both incised and burn wounds compared to the control group. Incised wounds fully healed by day 6, while burn wounds healed by day 7. This effectiveness is associated with the high total phenolic content (TPC) of the SCOBY gel, measured at 790.4 mg GAE/g extract, along with strong antioxidant activity of 12.42% (DPPH assay). Statistical analysis revealed a significant difference (p<0.05) in wound healing between the untreated and SCOBY gel-treated groups for both types of wounds. Therefore, kombucha SCOBY gel has potential as an effective natural topical wound-healing agent, particularly for mild to moderate wounds.   ABSTRAK (Bahasa Indonesia) SCOBY (Symbiotic Culture of Bacteria and Yeast) merupakan hasil fermentasi teh kombucha yang mengandung senyawa aktif, seperti asam fenolat dan flavonoid, yang memiliki aktivitas antioksidan tinggi. Namun penggunaan SCOBY hanya terbatas sebagai starter dalam pembuatan teh kombucha baru, sehingga diperlukan inovasi untuk meningkatkan manfaat lain dari SCOBY. Tujuan penelitian ini adalah untuk mengevaluasi efektivitas gel SCOBY kombucha dalam penyembuhan luka sayat dan luka bakar pada mencit (Mus musculus). Metode penelitian ini dimulai dari pembuatan teh kombucha, pemanenan SCOBY, pembuatan gel pengaplikasian pada luka sayat dan bakar pada mencit dan pengamatan penyembuhan luka sampai penutupan luka. Hasil penelitian menunjukkan bahwa gel SCOBY kombucha mempercepat penyembuhan luka sayat dan bakar secara signifikan dibandingkan kelompok kontrol. Luka sayat sembuh sempurna pada hari ke‑6, sedangkan luka bakar sembuh pada hari ke‑7. Efektivitas ini dikaitkan dengan tingginya kadar total fenolik (TPC) gel SCOBY, yaitu sebesar 790,4 mg GAE/g ekstrak, serta aktivitas antioksidan kuat sebesar 12,42% (uji DPPH). Hasil analisis statistik menyatakan pada luka sayat dan bakar terdapat perbedaan signifikan(p<0,05) antara kelompok tanpa perlakuan dan gel SCOBY. Dengan demikian, gel SCOBY kombucha berpotensi sebagai agen penyembuh luka topikal alami yang efektif, khususnya untuk luka ringan hingga sedang.